Competitive Skateboarding- Interdisciplinary perspectives on the discipline park - Büscher, B.; Charly, M.; Simbaña Escobar, D. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
Theory: As a theoretical figure, Skateboarding stands as an informal subculture building around the movement patterns of a roll sport in connection to the attribution of urban spaces, where the mostly adolescent participants reproduce an associated lifestyle (Borden, 2019). However, the integration into the Olympic Summer Games 2020 (2021) in Tokyo has triggered ongoing tendencies around the subculture`s "sportisation" (Kilberth & Schwier, p. 11) resulting in the incorporation of existing sports associations as well as the establishment of training facilities and programmes. Ongoing debates not only cover the partial transformation of the informal practice into more standardised and competitive log-ic of sport, but furthermore focus on the particularities of the newly evolved differentiations (Atencio et al., 2018). Method Focusing on the olympic discipline Park, research focuses on the terrain`s structure concerning the form and arrangement of ramps, obstacles and intersections, as well as the adaptive movement patterns in 45-second runs during which the athletes aim to perform a condensed presentation of a variety of tricks. The WST Park World Championship 2022 (executed in February 2023) was analysed, data was collected from the public results (rawmotion.com/WSTWC22S). Mean values of age and number of nationality participant was calculated for each phase (qualifiers, quarter, semi-final, final). R Studio was used to performed the statistical analysis. Kruskall Wallis test was chosen to compare the mean values because data was non parametric. Results 183 Athletes (65 F and 126 M) participated at the WST with four pressed athletes directly qualified directly to quarter final. Female athletes were younger that male athletes (16.6 **3.62 vs. 21.1**6.89, p<0.001***Nationality have an influence in the final score for male (F=73.2, p<0.01,*2= 0.40) and female (F=37.5, p<0.05,*2= 0.37). Only 3 nations were rep-resented at the final (M: USA, AUS and BRA, F: GBR, JPN and USA). Discussion Skateboarding is growing around the world, especially among young female athletes whose total number is lower than of male athletes. There were more nationalities represented (39 vs. 22) despite the nations obtaining the best score were the nations where the skateboard culture was largely represented. Countries need funding for new skate-parks matching Olympic norms to help athletes to improve training programmes and pre-pare for the competition. Stakeholders in each country need to continue to develop train-ing programs and promote the young talents in skateboarding competition.